PENGEMBANGAN POTENSI SISWA CERDAS INTELEKTUAL BERBAKAT ISLAMI MELALUI PROGRAM AKSELERASI - Imam Nawawi; Tatik Swandari (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2021)
This article aims to discuss the application of the Acceleration program in developing the Potential of Islamically talented Intellectual Students at Madrasah Tsnawiyah Sunan Giri Probolinggo. This article uses qualitative research with a case study approach with data collection techniques by observation, interviews and documentation. From research that focuses on efforts to streamline the recruitment process for accelerated student input, it is found that: 1) recruitment activities are carried out after the admission of new students to the regular program, 2) the recruitment process is carried out by a special committee consisting of teachers and a team of psychologists, 3) the recruitment process uses the test method. and non-test, 4) there is no classroom observation activity before the test, 5) the tests used consist of administrative tests, psychological tests, and academic potential tests, 6) interviews are non-test methods and are carried out both with participants and parents of participants, 7) Participants identified as intellectually gifted students are separated from regular students and placed in special accelerated classes. Furthermore, efforts to streamline teaching services in accelerated classes are carried out by: 1) adjusting teacher management for accelerated classes which includes adjustments to recruitment, coaching and awarding, 2) curriculum adjustments in the form of adjusting the time and speed of learning, learning methods, and learning materials to be taught. seen in PBM in accelerated classes, 3) adjustment of PBM which consists of creating a learning environment, choosing learning methods that can stimulate higher-order thinking processes supported by the application of PAKEM, ICT-based learning, enrichment, bilingual PBM, team teaching, module use, and BK activities involving psychologists.